Exosomes derived from LPS-stimulated human thymic mesenchymal stromal cells enhance inflammation via thrombospondin-1. Issue 10 (29th October 2021) - Li, Qianru; Li, Jing; Sun, Lei; Sun, Yun; Zhao, Fei; Liu, Pingping; Peng, Xin; Xuan, Xiaoyan; Li, Yun; Wang, Peng; Tan, Chen; Du, Ying
Abstract: Inflammatory response mediated by immune cells is either directly or indirectly regulated by mesenchymal stromal cells (MSCs). Accumulating evidence suggests that thrombospondin-1 (TSP-1) is highly expressed in response to inflammation. In this work, we isolated and identified human thymic mesenchymal stromal cells (tMSCs) and detected the expression of TSP-1. We found that tMSCs expressed TSP-1 and Poly (I:C) or LPS treatment promoted the expression of TSP-1. Further, we isolated and identified exosomes originating from tMSCs (MEXs). Notably, exosomes derived from LPS-pretreated tMSCs (MEXs LPS ) promoted the polarization of macrophages to M1-like phenotype and IL-6, TNF-α secretion as well as the pro-inflammatory differentiation of CD4 + T cells into Th17 cells. Upon silencing the expression of TSP-1 in tMSCs, the pro-inflammatory effects of MEXs LPS were suppressed. Therefore, these findings uncovered TSP-1 as the principal factor in MEXs LPS pro-inflammatory regulation.